2022
DOI: 10.1038/s41598-022-17782-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fermentation of chosen vegetables on the nutrient, mineral, and biocomponent profile in human and animal nutrition

Abstract: In the present study, the dry matter, crude ash, crude protein, ether extract, and energy, macro- (Na, K, Ca, Mg, P), micro- (Zn, Cu, Fe) minerals, heavy metals (Pb, Cd), vitamin C, A, carotene, and phenolic content were determined in chosen raw and fermented vegetables. The dietary intake of several macro- and microconstituents per one serving (100 g or humans and animals: ducks and pigs) was calculated. The fermentation process was found to reduce water and increase fat content in the vegetables. Lower level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 64 publications
2
18
0
Order By: Relevance
“…Fermentation decreases the TPC for gherkins from 40.3 ± 0.2 to 29.4 ± 1.4 mg GAE/100 g (P < 0.05); this value is similar with (Kiczorowski et al, 2022), but is lower than that found in another literature (Ciniviz et al, 2020). After the in vitro digestion process, TPC values for gherkins and pickled gherkins are increased to 149.1 ± 7.3 and 136.2 ± 11.2 mg GAE/100 g, respectively.…”
Section: Total Antioxidant Activity (Taa)supporting
confidence: 76%
“…Fermentation decreases the TPC for gherkins from 40.3 ± 0.2 to 29.4 ± 1.4 mg GAE/100 g (P < 0.05); this value is similar with (Kiczorowski et al, 2022), but is lower than that found in another literature (Ciniviz et al, 2020). After the in vitro digestion process, TPC values for gherkins and pickled gherkins are increased to 149.1 ± 7.3 and 136.2 ± 11.2 mg GAE/100 g, respectively.…”
Section: Total Antioxidant Activity (Taa)supporting
confidence: 76%
“…The occurrence of cholinesterase in fresh fruit products may decrease choline levels. Kiczorowski et al [22] found that the fermentation process in some fruits causes a relative decrease in some nutrients and biochemical compounds, but increases vitamins and fat, maintains their stability, and extends shelf life. Moreover, the fermentation process decreases the pH and heavy metals in fruits, preventing the oxidation of some nutrients, including vitamins, consistent with results from the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial fermentation can reduce the antinutrients in pig feed and improve the feed absorption and intestinal flora [ 3 ]. In fermented food or feed, the vitamin A and carotenoids content, and tyrosinase inhibitory and antioxidant activities, are noticeably increased [ 4 , 5 ]. Consequently, fermentation is a promising method to ameliorate the quality ingredients of foods, fodders, and traditional herbs.…”
Section: Introductionmentioning
confidence: 99%